Characterisation of the flow behavior of deep drawing steel grades in dependency of the stress state and its impact on FEA - Merklein, Marion; Sturm, Vera (International Journal of Material Forming, 2009)
In numerical simulation the flow behavior of the material is described by the flow curve under uniaxial stress condition. As within the tensile test experimental values can only be determined up to low strains, further experiments are applied in order to obtain higher strains. The alternative experiments are generally carried out under different stress conditions in comparison to the stress condition of the tensile test. Within this paper the differences in flow behavior under the respective stress conditions are figured out. Apart from the optical strain analysis of the tensile test after the onset of necking, the bulge test and the layer compression test are applied. Furthermore the work hardening of materials under different test conditions is compared. © Springer/ESAFORM 2009.
LFT Import::2019-07-29 (310)
Keywords: Deep drawing steel grades; Flow behavior; Stress condition